KONTRIBUSI HASIL BELAJAR BUSANA PESTA TERHADAP KESIAPAN UJI KOMPETENSI PEMBUATAN BUSANA PESTA - Cici Anggraeni; Pipin Tresna P (Universitas Pendidikan Indonesia, 2015)
Party dress is dress that uses for attending party events. In the making process of party dress is needed special skill, carefulness, seriousness to make a high quality of party dress. Party dress can be learned in one of skill programs, that is fashion skill program. This research examined the contribution of the learning outcomes of the readiness in party dress-making competency test. The method that wasused was descriptive eanalytic method. The research population was the third grade dress-makingskills program students of SMK Negeri 3 Cimahi with simple random sampling amounted to 41 students. Data collection tools were in the form of tests and questionnaires. The result showed the learning outcomes of party dress, party dress-making technique, and embroidery decoration on a party dress in general were at sufficient criteria and provide a significant positive contribution to readiness of the party dress-making competency test. The conclusion of this research is in learning party dress provides a substantial contribution to support the implementation of the readiness in party dress-making a competency test. Suggestion in this research is recommended to students that they should further improve their knowledge, attitudes and skills in making a party dress that can be used as a stepping-stone to test the implementation of party dress-making competency test.